‘Pedants’ vs ‘Mondains’ - On the Ways in Which Young People Interact in the Schooling Process Through the Lens of Pierre Bourdieu’s Theory of Habitus and Socio-Cultural Capital - Jurczak-Morris, Marta (INSTED: Interdisciplinary Studies in Education & Society, 2021)
School, like a social melting pot, is a space for diverse interactions and behaviours, often of quite a different nature. The aim of this text is to look at the ways in which pupils from varying social backgrounds interact with the school world as well as to explain the logic behind their behaviour. Pierre Bourdieu, whose theoretical approach forms the basis of my research, has dichotomised these types of interactions as ‘pedantism’, a characteristic of the so-called ‘humble pupils’, and ‘self-confidence’, that of the so-called ‘worldly pupils’ (‘mondains’), highlighting the fundamental differences in their modality to culture and language, manifested in their different ways of being and reacting within the school world. This text discusses these various ways of interaction with and at school based on pupils’ social class affiliation, highlighting specific situations from school life to illustrate the Bourdieusian theory of capital and habitus.